About the Competent Court in the Matter of a Litigation Regarding the Annulment of a Decision Whose Object Is the Release from a Public Management Position - Radu Stefan Patru (Perspectives of Law and Public Administration, 2023)
The present study will analyze the aspects related to the competent court in the matter of the request for annulment of a decision ordering the release from a public management position, from the perspective of decision no. 5746/2022 of the High Court of Cassation and Justice. The supreme court in Romania established that in the mentioned situation the provisions of the Administrative Code prevail over the provisions of Law no. 554/2004 of the administrative litigation. This decision, which is based on a litigation registered before the Dolj Court, has a particularly important role in the matter of jurisdiction in a delicate issue of administrative law.